Pharmacists' knowledge, attitudes, beliefs, and barriers toward breast cancer health promotion: a cross-sectional study in the Palestinian territories - Ramzi Shawahna; Hiba Awawdeh (BMC, 2021)
Abstract Background Among all cancers, breast cancer is the most prevalent cancer and the leading cause of mortality among women in developing countries including Palestine. Community pharmacists are trusted and easily accessible healthcare providers who could be engaged in breast cancer health promotion. This study was conducted with the aim of exploring knowledge, attitudes, beliefs, and barriers toward breast cancer health promotion among community pharmacists in the Palestinian territories. Methods This study was conducted in a cross-sectional design using a questionnaire among community pharmacists. Knowledge of community pharmacists of breast cancer was tested using a 26-item knowledge test. Attitudes and beliefs of the community pharmacists with regard to breast cancer promotion were explored using 14 items. Barrier to breast cancer health promotion were explored using 9 items. Results Data were collected from 200 community pharmacists. The median knowledge score was 69.2 % with and IQR of 15.2 %. Of the community pharmacists, 67.5 % scored 50 % and above in the knowledge test. Multivariate logistic regression showed that community pharmacists who were female in gender were more likely to score 50 % and above in the knowledge test compared to the community pharmacists who were male in gender (OR = 4.73, 95 % CI of 2.26-9.89). The community pharmacists had positive attitudes toward breast cancer health promotion. There was a significant moderate positive correlation between knowledge and attitudes scores (Spearman's rho = 0.37, p-value < 0.001). Lack of reimbursement, lack of enough personnel, lack of time, and fear of offending the patients were the main barriers to breast cancer health promotion (percentage of agreement > 60.0 %). Conclusions This study shed light on the role of community pharmacists in breast cancer health promotion. Pharmacists had good knowledge of breast cancer and positive attitudes toward promoting the health of patients with breast cancer. Further studies are still needed to determine how to integrate community pharmacists in the team of healthcare providers caring for patients with breast cancer.